Optimization of poly(vinylidene fluoride) membranes for enhanced power density of thermally driven electrochemical cells - Hasan, S.W.; Said, S.M.; Bakar, A.S.A.; Sabri, M.F.M.; Sajid, I.H.; Hashim, N.A. (Kluwer (now part of Springer), 2017)
The thermally driven electrochemical cells (TECs) convert the applied temperature gradient (ΔT) across electrodes, in redox-based electrolytes, into electricity. We, in this report, amplify the power generation characteristics of TEC, maintained at the ΔT of 45 K, by controlling the physical and electrical nature of the polymer membrane. The conductive membrane is prepared by trapping the solution of iodide/triiodide (I−/I3 −) and 1-butyl-3-methylimidazolium tetrafluoroborate [C4mim][BF4] in the mesoporous structure of poly(vinylidene fluoride) membranes. We identify the intricate dependence of TEC performance on numerous thermophysical and electrical properties including thermal conductance, porosity, thickness and ionic resistance of the membrane. Higher thickness provides better thermal resistivity maintaining the TEC at high ΔT; however, this simultaneously reduces the porosity (limiting the redox reactions at the electrodes) and augmenting the membrane resistance. Therefore, a compromise between high thermal gradient and availability of redox species at electrodes improves the maximum power density from 1.5 to 16.3 mW m−2.